"Bouncing Back" From a Loss: Entrepreneurial Orientation, Emotions, and Failure Narratives. (21st July 2013) - Wolfe, Marcus T.; Shepherd, Dean A.
<x xml:space="preserve">Abstract</x> In this study, we explore how failure in the form of the first lost game of the college football season for a team influences specific content within the narratives constructed regarding that loss and how those narratives are associated with subsequent performance. Building on theoretical perspectives regarding sports management, entrepreneurial orientation (EO), emotions, and the use of narratives for sensemaking, we develop and test an EO‐related sports management model of failure narratives. Using computer‐aided text analysis of transcripts from head coaches' press conferences directly following their team's first loss of the season as well as regression analysis, we found that the narrative's EO content has a U‐shaped relationship with subsequent (i.e., next game) performance. Additionally, negative emotional content had a similar U‐shaped relationship with subsequent performance. Finally, positive emotional content exhibited an inverse U‐shaped relationship with subsequent performance. We discuss the implications of these results on the literatures regarding EO, emotions, and sports management as well as possible avenues for future research.